URGENCY OF LEADERSHIP MANAGEMENT IN ISLAMIC EDUCATION INSTITUTIONS: URGENSI MANAJEMEN KEPEMIMPINAN DALAM LEMBAGA PENDIDIKAN ISLAM - A'yuni, Qurnia; Rindaningsih, Ida (Antis-Publisher, 2024)
This research aims to explain the study related to the urgency of leadership management in Islamic educational institutions. The research method used in this study is a qualitative research method with a library approach. By collecting reading materials sourced from reference books, journals, and some teaching materials that are in accordance with the research. The results of this study indicate that leadership management in educational institutions is a very important component. Because leadership management has an important role in shaping the quality and success of the institution. The principal as the main leader has a great responsibility in directing, organizing, and motivating all members of the institution to achieve the goals of the educational institution that has been set. Leaders can not only give orders to their subordinates, but can also influence the way they perform the task. The concept of leadership in Islam highlights the importance of exemplary traits, wisdom and the ability to give meaning to collective work. In the leadership management of Islamic educational institutions, leaders need to have strong leadership traits, problem-solving abilities, social skills and professional knowledge.